Forced Degradation Studies for Glycopyrrolate, Formoterol & Budesonide By UPLC - Darugu, Chowdeswari Darugu; Rao, B. Prasada; Anuradha, Ch.S.; kumar, J. Santosh; Rani, S. Shobha (International Journal of Membrane Science and Technology, 2023)
Forced degradation studies include the degradation of new drug substance and drug product at conditions more severe than accelerated conditions. These studies illustrate the chemical stability of the molecule which further facilitates the development of stable formulation with suitable storage conditions. ICH guidelines demonstrate certain degradation conditions like light, oxidation, dry heat, acidic, basic, hydrolysis etc.